A Diversidade Cultural e o Desenho Infantil: um diálogo que incide sobre a Formação Docente - Andrade, Mônica Borges de (2010)
Starting from the assumption that the design brings language mechanisms guided by the existence of an intent of those who produce, this study aimed to investigate how ethnic issues are conceived, understood and effect the practices adopted by teachers, considering that the design must oportunizar children from disclosing their historical and cultural imaginary and not only meet the standards set centered on a single european culture. Os standards outlined by the research subjects were two teachers at a public school in city of Feira de Santana, located in an area considered quilombo. We adopted a qualitative approach, developing the form of action research is reassuring, therefore, the commitment of the school as an instrument for the emancipation of the subjects. The results point to the need for teacher training that includes studies related to the insertion of the drawing at school, as well as others related to culture diversity in order to allow the children to be in his drawings reveals the culture african descent are often silenced by society.